A highly selective fluorescent probe for in vitro and in vivo detection of Hg2+ 1. Issue 19 (7th October 2015) - Zhou, Quan; Wu, Zeming; Huang, Xiaohua; Zhong, Fenfen; Cai, Qingyun
<x xml:space="preserve">Abstract</x> In this paper, a simple fluorescent probe, rhodamine B derivatives (RS), was designed and prepared for sensitive detection of Hg2+ in CH3CN/H2O (5/5, v/v).